APPLICATION OF NON PREEMPTIVE PRIORITY QUEUING FOR BASRAH COMMERCIAL PORTS - Zaki Naji, Huda; Abdul Razzaq, Suaad; Adnan, Samaher (Al-Qadisiyah Journal of Pure Science, 2019)
Waiting for commercial vessels inside the port is one of the most important problems facing traders and offshore companies, which often lead to material losses. The ports of Basrah are characterized by continuous congestion, which leads to the diversion of ships to the ports of the neighboring countries, causing the loss of many revenues to the country. This paper emphasizes the importance of non-preemptive priority queues (with multiple servers and multiple priority classes) to the problem of congestion of ports in order to promote sustainable development of the ports of Basrah. The aim of this paper is to apply a non-preemptive priority queues at ports of Basrah and calculating the average customer waiting time for the ships at berths.